Hubungan Stunting dengan Angka Kejadian Diare pada Siswa Sekolah Dasar di Kecamatan Tikala Manado - Taliwongso, Fernando Ch.; Manoppo, Jeanette I.Ch.; Umboh, Adrian (e-CliniC, 2017)
Abstract: Stunting is a chronic undernutrition problem due to various factors during childhood growth. Nutrition status at school age needs to be a concern, because undernutrition/malnutrition will cause children become more vulnerable to be infected by any disease. Currently, stunting rate at school is still a big problem. This study was aimed to determine the relationship of stunting with the incidence of diarrhea in elementary school students at Tikala, Manado. This was an observational analytical survey study with a cross-sectional design, conducted on 60 primary school students at Tikala, Manado. The results showed that there were 31 stunting children; 16 males (51.6%) and 15 females (48.4%). The highest percentage of stunting children was at age 9 years (10 of 31 samples). Statistical analysis showed that there was a significant relationship between stunting and the incidence of diarrhea (P=0.032). Conclusion: There was a significant relationship between stunting and the incidence of diarrhea among elementary school students at Tikala, Manado.Keywords: stunting, diarrhea, school-age childrenÂ Abstrak: Stunting merupakan masalah kurang gizi kronis yang disebabkan oleh berbagai faktor pada masa pertumbuhan anak. Status gizi pada usia sekolah perlu menjadi perhatian, karena status gizi yang kurang akan mempermudah anak untuk terinfeksi penyakit. Saat ini angka stunting pada usia sekolah masih menjadi masalah. Penelitian ini bertujuan untuk mengetahui hubungan stunting dengan angka kejadian diare pada siswa sekolah dasar di Kecamatan Tikala Manado. Jenis penelitian ialah survei analitik observasional dengan desain potong-lintang yang dilakukan pada 60 siswa sekolah dasar di Kecamatan Tikala Manado. Hasil penelitian menunjukkan bahwa terdapat 31 sampel anak stunting; 16 anak laki-laki (51,6%) dan 15 anak perempuan (48,4%). Persentase tertinggi anak stunting pada usia 9 tahun yaitu 10 dari 31 sampel anak stunting. Hasil uji statistik mendapatkan adanya hubungan bermakna antara stunting dan angka kejadian diare (P=0,032). Simpulan: Terdapat hubungan bermakna antara stunting dan angka kejadian diare pada siswa sekolah dasar di Kecamatan Tikala Manado.Kata kunci: stunting, diare, anak usia sekolah